Investigation of Mixture of Epoxy Resin/Palm Kernel Shell as Insulation - Murdiya, Fri (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2017)
Palm kernel shells have a high mechanical strength and good insulation strength. From these results it can be concluded that breakdown voltage of epoxy resin/palm kernel shells is higher than pure resin or resin/alumina. The highest breakdown voltage that occurred in the resin/palm kernel shells (8 wt%) is 76 kV. While the highest breakdown voltage that occurred in the epoxy resin/alumina (17 wt%) is 57.15 kV. Breakdown voltages of both samples are higher than the pure epoxy resin of 36 kV. The maximum electric field density (Emax) in the pure resin is 0.24 MV/cm that is lower than the resin/palm kernel shell (8 wt%) of 0.51 MV/cm and the resin/alumina (17 wt%) of 0.38 MV/cm. Discharge current has a lot of pulses and high amplitude when all solid insulation approached the breakdown event. However, the current pulses in the pure resin are higher than in both resin/palm kernel shell and resin/alumina. The epoxy resin mixture with palm kernel shells can be used as a new solid insulator.